Perancangan Sistem Proteksi Eksternal Penyalur Petir di Workshop PT. Bukaka Teknik Utama Balikpapan - Dimas pangestu Danar Putra; Mayda Waruni Kasrani; A. Asni B (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2023)
Abstract— PT Bukaka Teknik Utama is currently building a fairly spacious workshop building with a length of 60m, a height of 15m and a width of 20m which almost the entire building is made of steel. Considering that thunder days in the city of Balikpapan are quite high, which is as high as 227 per year, the building is vulnerable to lightning strikes. Therefore, to avoid the impact of the lightning strike effect, an external lightning protection system is needed. The method to be used in determining lightning protection is the rolling ball method. Because the shape of the building has a horse gable type the protection level is at level IV with a protection radius of 100.9m and is able to protect lightning currents up to 234.89 kA. After simulation using Sparkta software, the standard rolling ball method NFPA 780 and BS 7430 obtained detailed risk assessment calculation results which are quite safe.